Effects of Motorcycle Flashing Brake Lamp on The Rear Vehicle Based on Video Simulation - Abang Abdul Rahman, Abang Idlan Izzuddin; Mustafa, Norrizal (Progress in Engineering Application and Technology, 2022)
Accidents regarding vehicle collision occurs very often and a study was conducted and the results showed that warning systems (visual, audible and/or tactile) would lead to reduced crashes and shorter brake response times. The purpose of this study is to evaluate the effectiveness of motorcycle brake lamp when applying flashing brake lamp by using survey based in video simulation. The survey was made using Google Form and sent to random 50 respondent in Edu Hub Pagoh population. A few factors that brought major influence to Brake Reaction Time such as Age, Gender, Traumatic Experience, Medicinal Prescription and Driving Experience were chose as variable for this study. Statistical Package for the Social Sciences (SPSS) software is used to sort and analyze the obtained data. Results shows that flashing brake light seems to improve the Brake Reaction Time in most cases in all factors that is discussed. This study majorly adds to the body of knowledge relating to flashing brake light with brake reaction time.